2016
DOI: 10.4238/gmr.15028077
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased expression of miR-874 and its tumor suppressive function in human colorectal cancer

Abstract: ABSTRACT. Dysregulation of miRNAs is associated with cancer development and progression. For example, aberrant expression of miR-874 has been found in some types of cancer. However, miR-874 expression and its clinical significance in colorectal cancer (CRC) have not yet been explored. The aim of the current study was to explore the effects of miR-874 in CRC tumorigenesis and development. Quantitative reverse-transcription PCR was performed to evaluate miR-874 levels in CRC cell lines and in 135 pairs of prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Up-regulation of miR-874 weakened the colony-forming ability of CRC cells and increased the sensitivity of CRC cells to 5-fluorouracil. Wang et al 21 suggested miR-874 to be a novel therapeutic target for CRC, and low expression of miR-874 in CRC was an independent predictor of low survival. Results from this article also revealed that, as a tumor suppressor, miR-874 expression was reduced in CRC and was directly inhibited by circ_0005576.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of miR-874 weakened the colony-forming ability of CRC cells and increased the sensitivity of CRC cells to 5-fluorouracil. Wang et al 21 suggested miR-874 to be a novel therapeutic target for CRC, and low expression of miR-874 in CRC was an independent predictor of low survival. Results from this article also revealed that, as a tumor suppressor, miR-874 expression was reduced in CRC and was directly inhibited by circ_0005576.…”
Section: Discussionmentioning
confidence: 99%